Social comparison and gender differences in risk taking - Ulrich Schmidt; Andreas Friedl; Katharina Lima de Miranda (Kiel Institute for the World Economy (IfW), 2015)
The present paper contributes to the controversy regarding gender differences in risk taking by investigating the impact of social comparison. Social comparison is formalized by integrating a social reference point into the model of Köszegi and Rabin. Drawing on previous results from evolutionary biology, we hypothesize that men (women) focus more on relative (absolute) income, i.e., the relative weight of social gain-loss utility is higher for men than for women. Our model predicts that risk taking is higher for correlated than for uncorrelated risks and that this effect is stronger for men than for women. These predictions are confirmed by a simple classroom experiment. We conclude that social comparison and the correlation of risks play an important role in the discussion of gender differences in risk taking.
Keywords: C91; D81; J16; 330; risk taking; gender differences; correlation of risks; social reference point